Construction of an evaluation indicator system for the emergency management capability of major infectious diseases in urban communities - Xiuying Guan; Wentao Li; Nan Cui; Jiacen Yu; Libin An (BMC Health Services Research)
Abstract Objective From a community-based perspective, this study aims to scientifically construct an evaluation indicator system for assessing the emergency management capacity of urban communities in response to major infectious diseases. Methods A research team was established to oversee the selection of the theoretical framework and principles for constructing indicators. This team defined the first-level and second-level indicators, developed a pool of third-level indicator candidates, conducted a Delphi expert consultation, and finalized the third-level indicators based on the consultation results. This study aims to analyze theories of emergency management, co-construction, co-governance, and shared benefits to identify relevant first- and second-level indicators. The Octopus big data collection tool was employed to gather policies related to infectious diseases and emergency responses. Through theoretical analysis, the entities responsible for managing emergencies during major infectious disease outbreaks in urban communities were identified, informing the selection of subsequent third-level evaluation indicators. A systematic literature retrieval strategy was developed, encompassing both domestic and international publications on emergency management capacity. The literature was categorized into two groups: those with and those without a direct relation to the evaluation indicator system. Based on the identified second-level indicators, relevant literature was extracted, supplemented by additional materials from non-evaluation categories. The outcomes of the literature review were presented to the research team for deliberation on the selection of third-level indicators, ensuring alignment with established principles for constructing indicator systems. This process integrated theoretical foundations with findings related to identified responsible entities, resulting in an initial evaluation indicator system. The modified Delphi method was applied to refine the third-level indicators for the evaluation system. Indicators were selected on the basis of the mean importance values and coefficients of variation, leading to the establishment of the final evaluation system. Hierarchical analysis was employed to validate the structure of the evaluation indicator system for assessing emergency management capacity in urban communities during major infectious disease outbreaks, with weights systematically assigned. Results Twenty-two experts were invited to participate in three rounds of opinion solicitation, and the positive coefficient of experts was 1.0, the average authority coefficient was 0.88, and the Kendall’s W coefficient of the third round was 0.175 (P < 0.001). This system consisted of 4 first-level indicators, 19 second-level indicators, and 54 third-level indicators. Conclusion The developed evaluation indicator system for emergency management capabilities in urban communities regarding major infectious diseases demonstrates both innovation and scientific rigor, with a well-considered allocation of weights. This system serves as a crucial reference for the collaborative efforts of various stakeholders in managing emergencies associated with significant infectious disease outbreaks in urban areas. Furthermore, it provides a systematic framework for assessing the emergency management capabilities of urban communities in response to major infectious disease epidemics.